Bringing the transgovernmental in: the public service in the Canada-United States relationship - Gattinger, Monica (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2004)
This article examines an often-overlooked dimension of Canada-United States relations : relations between Canadian and American public servants. Meetings between political leaders of Canada and the US may make front-page headlines, but it is the myriad of networks and interconnections between Canadian and American public servants that constitute the lion’s share of bilateral activity. Notwithstanding the multitude of daily cross-border, inter-departmental, and inter-agency interactions, there has been relatively little systematic theoretical or empirical attention to the public sector dimension of Canada-US relations. Public administration scholars tend to train their sights on the domestic level and pay little or no attention to the public management dimension of international affairs. A recently edited volume studying contemporary Canadian public administration does not examine these relations. International relations scholars, for their part, tend to oversimplify domestic politics and policy institutions. This text contributes to bridging this gap in the literature. It builds on the concept of transgovernmentalism, relations between legislative, executive, regulatory, and judicial players with their international counterparts. It examines the mechanisms and processes by which public sector players interact across borders (e.g., informal relations, formal agreements, joint organizations, etc.). The article explores the relationship between the degree of bilateral policy coordination in a policy field or issue area and the mechanisms of transgovernmental activity characterizing cross-border relations in that policy domain.